A mechanistic and stochastic approach to fatigue crack nucleation in coarse grain RR1000 using local stored energy - Pan,YB; Dunne,FPE; MacLachlan,DW (Fatigue and Fracture of Engineering Materials and Structures, 2021)
The crystal plasticity finite element (CPFE) method is used in conjunction with a critical local stored energy criterion to predict crack nucleation life for Coarse Grain (CG) nickel superalloy RR1000. Artificial representative microstructures are generated using Dream3D, and through simulation of multiple microstructural instantiations, a distribution of simulated fatigue response is generated. Fatigue of CG RR1000 is studied at 300°C and 700°C and at two R ratios of R = 0.1 and R = −1 giving a range of conditions to test the stored energy method. At higher temperature failure frequently occurs from inclusions, these are represented in the model by adding an inclusion with cohesive zones between inclusion and matrix. The results at 300°C are very good with the one parameter model (the critical stored energy) able to predict the mean, slope and distribution of fatigue data. At 700°C, the results are also good; however, fatigue life at high strain amplitude is overpredicted.